Особливості мотивації навчальної та професійної діяльності в студентському віці - Полоус, В. Ю. (ХНУРЕ, 2023)
This work highlights the importance of motivation in student's life. Intrinsic motivation promotes deep learning and long-term retention, while extrinsic motivation can lead to superficial knowledge. A balance between both types is necessary for success, and educators play a crucial role in creating supportive environments. Motivation is influenced by individual and sociocultural factors, making it essential for educational institutions to prioritise diverse needs and promote psychological well-being.